Sports participation and its implication on the academic performance of students in tertiary institutions in Nigeria: A literature review - Alasinrin, Semiu; Ajeigbe, Issa Yaqub (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
The study focused on sports participation and its implication on the academic performance of students in tertiary institutions in Nigeria. To ascertain the objective of the study, the study focused on Overview of sports, Sports participation, Implication of sports on academic performance of students and Benefits of Sports Performance on academic Performance of Students however, concluded that, sports participation would have no negative implication on students’ academic performance in tertiary institutions. The study also concluded that students of tertiary institution in Nigeria should not be discouraged from participating in sports with the misconception that participation in sports worsens students’ general performance and specifically performance of students of tertiary institution. What this study implies is that, coaches, lecturers and school management should not seize students from participating in sporting activities as this go a long way in assisting them in all ramifications. It was suggested that future researcher should broaden the scope of the study to at least two to three countries so as to encourage participation in sports. It was further suggested that the Study should be conducted on the effects of sports participation among secondary and primary school students in Nigeria.